2004
DOI: 10.1023/b:emas.0000003566.63111.f6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Pesticidal Contamination of Farmgate Vegetables from Hisar

Abstract: Analysis of 84 farm gate samples of seasonal vegetables carried out on GC-ECD and GC-NPD systems equipped with capillary columns by using a multi residue analytical technique revealed that 26% samples contained residues above MRL values. The contamination was mainly with organophosphates followed by synthetic pyrethroids and organochlorines. Among organophosphates, residues of monocrotophos, quinalphos and chlorpyriphos exceeded the MRL value in 23% samples. Residues of monocrotophos were higher than MRL value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 1 publication
4
62
0
Order By: Relevance
“…Contamination of vegetables with pesticide residues has been reported by several researchers (Madan et al, 1996;Kumari et al, 2002Kumari et al, , 2003 and washing was found effective in dislodging the residues as it depends on a number of factors like location of residues, age of residues, water solubility and temperature and type of washing. In earlier studies also, effects of these factors were observed in different vegetables by various researchers Lal, 1982a, 1982b;Dikshit et al, 1986;Geisman, 1975;Gunther et al, 1963).…”
Section: Resultsmentioning
confidence: 98%
“…Contamination of vegetables with pesticide residues has been reported by several researchers (Madan et al, 1996;Kumari et al, 2002Kumari et al, , 2003 and washing was found effective in dislodging the residues as it depends on a number of factors like location of residues, age of residues, water solubility and temperature and type of washing. In earlier studies also, effects of these factors were observed in different vegetables by various researchers Lal, 1982a, 1982b;Dikshit et al, 1986;Geisman, 1975;Gunther et al, 1963).…”
Section: Resultsmentioning
confidence: 98%
“…Likewise, a greater risk of developing asthmatic symptoms and low respiratory volumes has been reported in farmers chronically exposed to pesticides 8) . Currently, India is the largest producer of pesticides in Asia and the third largest consumer of pesticides in the world 9) . A vast majority of the one billion-plus population in India is engaged in agriculture as cultivators, farm owners and laborers.…”
mentioning
confidence: 99%
“…Most of the studies on pesticides conducted in Asia reflect the presence of pesticide residues in significant amounts in food and agricultural commodities, and pesticide pollution does exist in the country; and is a cause of concern for public health (Kumari et al 2002(Kumari et al , 2003(Kumari et al , 2004(Kumari et al , 2005(Kumari et al , 2006. Pesticides applied to the soil or that eventually end in the soil in agricultural areas can contribute to the contamination of surface and ground waters (Gilliom et al 2006;McMahon et al 2006).…”
Section: Status On Pesticide Related Issuesmentioning
confidence: 99%